Blast Fishing in the Philippines, with Notes on Two Destructive Fishing Activities - Alcala, Angel C. (Silliman Journal, 2022)
Blast fishing has been considered a destructive method of fishing because it destroys coral reef habitats and fishery stocks as well as other marine or-ganisms. Although a number of studies have documented the extent of its occur-rence in some parts of the Philippines where it is cawing considerable damage to places such as the Palawan group of islands, the Sulu archipelago, and the western Mindanao, there is also evidence that the incidence of blast fishing has declined or ceased in some areas of the country. This generally decreasing trend in the incidence of blast fishing is attributed mainly to the increased environ-mental awareness of people as a result of educational campaigns against de-structive fishing activities, the vigorous implementation offishery laws by some local government units and, more importantly, the depletion in coastal areas of schooling fish, which are the primary targets of blast fishermen. An economic analysis of blast fishing provides evidence that while indi-vidual fishers derive substantial financial benefits from blast fishing, the net loss to society after years is substantial, a good reason to eliminate blast fishing on coral reefs. Two other fishing activities—spear fishing with scuba or "hookah" compressor and drift gill net fishing—also deplete marine resources. Spear fish-ing with scuba should be banned. Drift gill net fishing should be regulated to minimize its potential negative impact on fish, marine mammals, and other marine species. The development of alternative fishing activities or sources of income to which spear fishers, drift gill net operators, and blast fishers can shift their fishing operations is highly desirable.